2015
DOI: 10.1002/cctc.201500605
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Reduction with Short‐Chain Dehydrogenases: Tetrahydroxynaphthalene Reductase, Trihydroxynaphthalene Reductase, and Glucose Dehydrogenase

Abstract: NAD(P)H‐dependent oxidoreductases from the short‐chain dehydrogenases/reductases (SDRs) family possess high functional diversity. Three SDRs, namely, tetrahydroxy‐ and trihydroxynaphthalene reductases (T4HNR, T3HNR) involved in the dihydroxynaphthalene‐melanin biosynthesis of the phytopathogenic fungus Magnaporthe grisea, and glucose dehydrogenase (GDH) from Bacillus subtilis, were characterized regarding their substrate range and functional behavior. T4HNR and T3HNR share activities towards the stereoselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 43 publications
2
43
0
4
Order By: Relevance
“…The high reactivity of the iminium salts towards reduction was probably helpful for elucidation of the entirely unexpected asymmetric reduction of a C=N bond by GDH, usually regarded as a “classical” NADPH‐dependent SDR . Hence, we have demonstrated that the substrate scope of GDH is broader than initially suspected, underscoring our previous finding of GDH‐catalyzed reduction of naphthoquinone derivatives . The enantioselectivity of the iminium reduction is strikingly high, even being higher than for many IRED‐catalyzed transformations.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…The high reactivity of the iminium salts towards reduction was probably helpful for elucidation of the entirely unexpected asymmetric reduction of a C=N bond by GDH, usually regarded as a “classical” NADPH‐dependent SDR . Hence, we have demonstrated that the substrate scope of GDH is broader than initially suspected, underscoring our previous finding of GDH‐catalyzed reduction of naphthoquinone derivatives . The enantioselectivity of the iminium reduction is strikingly high, even being higher than for many IRED‐catalyzed transformations.…”
Section: Methodssupporting
confidence: 90%
“…Glucose dehydrogenase (GDH), a prototypical member of the SDR family, for example, was previously thought solely to catalyze NAD(P)‐dependent oxidation of d ‐glucose to gluconolactone . Until recently, GDH was not known to be active with non‐sugar substrates …”
Section: Methodsmentioning
confidence: 99%
“…Thed earomatization reaction is enabled by the 1,3,5-arrangement of the three hydroxy groups of 1,w hich results in at endency towards distinct tautomerization and thus favors nucleophilic attack on the oxo carbon groups. [8] Patel et al have shown the NADPH-dependent reduction of 1 into 2 by ap artially purified phloroglucinol reductase (PGR) from Coprococcus sp., which has am olecular weight of about 130 kDa. [7] Such biocatalytic dearomatization reactions are frequently found in the bio-synthesis of secondary metabolites as at ool for deoxygenation, which in this case would result in resorcinol (3; Scheme 2).…”
mentioning
confidence: 99%
“…[9] Fermentative degradation of gallic acid (4), pyrogallol (5), 2,4,6-trihydroxybenzoic acid (6), and 1 was reported in apure culture of Pelobacter acidigallici gen. nov.s p. nov. [10,11] Here too,the pathway was assumed to proceed via 2. [8,[15][16][17][18] Theenzymatic dearomatization of polyhydroxylated benzenes should be possible in as imilar manner. [3,12,13] Haddock and Ferry have described the purification of aPGR from the cell extract of E. oxidoreducens.The described enzyme,which has an ative molecular weight of 78 kDa (homodimer), was specific for 1 and NADPH.…”
mentioning
confidence: 99%
“…The group of Vladimir Kren has been active in oligosaccharide synthesis for years and provides a contribution on prokaryotic and eukaryotic aryl sulfotransferases and their use in sulfation of quercetin . The group of Michael Müller in Freiburg point out that short chain dehydrogenases have a much higher functional and stereochemical diversity than had been previously thought …”
mentioning
confidence: 99%